Resin composition, cured product, polarizing plate, image display device
Patent Information
- Application Number
- JP2020025302
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-02-18
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-02-18
AI Technical Summary
【0028】 以上説明したように本発明によれば、耐擦傷性および耐屈曲性に優れ、偏光子の保護層として使用可能な硬化物を形成することができる。
Smart Images

Figure 0007638624000007 
Figure 0007638624000001 
Figure 0007638624000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a cured product, a polarizing plate, and an image display device. [Background technology]
[0002] An image display device such as a liquid crystal display includes a polarizing plate. The polarizing plate includes a polarizer and a protective layer provided on at least one surface of the polarizer. Conventionally, a protective film having a thermoplastic resin film (film substrate) such as triacetyl cellulose (TAC) or polyethylene terephthalate (PET) and a hard coat layer provided on at least one surface of the resin film has been used as the protective layer for the polarizing plate (for example, see Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-66365 A Summary of the Invention [Problem to be solved by the invention]
[0004] Conventional protective films having a resin film and a hard coat layer have a limit on how thin they can be made. Therefore, when the protective film is used in a mobile terminal or the like, there is a problem that the thickness of the protective film is too large. In addition, conventional protective films have a problem that they become thick in order to have scratch resistance, bending resistance, and a function of protecting a polarizer.
[0005] Therefore, an object of the present invention is to provide a resin composition capable of forming a cured product having excellent scratch resistance and flex resistance and usable as a protective layer for a polarizer. Another object of the present invention is to provide a cured product of the resin composition, a polarizing plate including the cured product as a protective layer for a polarizer, and an image display device including the polarizing plate. [Means for solving the problem]
[0006] In order to solve the above problems, according to one aspect of the present invention, there is provided a resin composition comprising a cellulose acylate (A), a polyfunctional (meth)acrylate (B), a crosslinking agent (C), and a photoradical initiator (D), wherein the content of the polyfunctional (meth)acrylate (B) is 100 parts by mass or more and 1,000 parts by mass or less per 100 parts by mass of the cellulose acylate (A).
[0007] According to this aspect, it is possible to form a cured product that has excellent scratch resistance and bending resistance and can be used as a protective layer for a polarizer.
[0008] The crosslinking agent (C) may have two or more isocyanate groups in one molecule, and the content of the isocyanate groups may be 0.1 to 5 times the content of the hydroxyl groups in the cellulose acylate (A).
[0009] According to this aspect, the crosslinking agent (C) can crosslink with the cellulose acylate (A).
[0010] The cellulose acylate (A) may have R=at least one selected from the group consisting of acetate, propionate and butyryl groups.
[0011] According to this aspect, the crosslinking agent (C) can crosslink with the cellulose acylate (A).
[0012] The content of the photoradical initiator (D) may be 0.1 parts by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the cellulose acylate (A).
[0013] According to this aspect, the polyfunctional (meth)acrylate (B) is crosslinked by irradiation with light, and a cured product that has excellent scratch resistance and bending resistance as a single layer and can be used as a protective layer for a polarizer can be formed.
[0014] Furthermore, an ultraviolet absorber (E) may be contained.
[0015] According to this aspect, a cured product having excellent durability against ultraviolet light can be formed.
[0016] The content of the ultraviolet absorber (E) may be 0.1 parts by mass or more and 25 parts by mass or less with respect to 100 parts by mass of the cellulose acylate (A).
[0017] According to this aspect, a cured product having excellent durability against ultraviolet light can be formed.
[0018] The crosslinking agent (C) may have two or more isocyanate groups and one or more acrylate groups in one molecule.
[0019] According to this aspect, the crosslinking agent (C) can crosslink with the cellulose acylate (A) and the polyfunctional (meth)acrylate (B).
[0020] According to another aspect of the present invention, there is provided a cured product of the resin composition of the present invention, which has a transmittance of light with a wavelength of 380 nm of 10% or less.
[0021] According to this aspect, the resin composition has the same level of ultraviolet absorbing properties as a protective film, and when the cured resin composition is used as a protective film for a polarizing plate, it can suppress the incidence of ultraviolet rays on a polarizer or the like.
[0022] The thickness may be 25 μm or less.
[0023] According to this aspect, when the cured resin composition is used as a protective film for a polarizing plate, the thickness of the polarizing plate can be reduced.
[0024] According to another aspect of the present invention, there is provided a polarizing plate comprising a polarizer and a protective layer provided on at least one surface of the polarizer, the protective layer comprising the cured product of the present invention.
[0025] According to this aspect, a polarizing plate having excellent scratch resistance and bending resistance can be obtained.
[0026] According to another aspect of the present invention, there is provided an image display device comprising an image display element and polarizing plates respectively provided on one side and the other side of the image display element, the polarizing plates being made of the polarizing plate of the present invention.
[0027] According to this aspect, an image display device having excellent scratch resistance and bending resistance can be obtained. Effect of the Invention
[0028] As described above, according to the present invention, it is possible to form a cured product that has excellent scratch resistance and bending resistance and can be used as a protective layer for a polarizer. [Brief description of the drawings]
[0029] [Figure 1] 1A to 1C are schematic diagrams illustrating an example of a method for producing a polarizing plate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] A preferred embodiment of the present invention will now be described in detail.
[0031] [Resin composition] A resin composition according to one embodiment of the present invention will be described. The resin composition according to this embodiment is used to form a protective layer provided on at least one surface of a polarizer.
[0032] The resin composition of the present embodiment contains cellulose acylate (A), polyfunctional (meth)acrylate (B), crosslinking agent (C), and photoradical initiator (D). That is, the resin composition of the present embodiment contains at least cellulose acylate (A), polyfunctional (meth)acrylate (B), crosslinking agent (C), and photoradical initiator (D), and is a mixture of these components.
[0033] (Cellulose acylate (A)) The cellulose acylate (A) preferably has R=at least one selected from the group consisting of acetate, propionate, and butyryl groups, and preferably has an acyl group having a carbon atom number in the range of 2 to 4. Examples of the acyl group having a carbon atom number in the range of 2 to 4 include an acetyl group, a propionyl group, and a butanoyl group.
[0034] The β-1,4-bonded glucose units that make up cellulose have free hydroxy groups at the 2-, 3-, and 6-positions. Cellulose acylate is a polymer in which some or all of these hydroxy groups are acylated with acyl groups. The total degree of acyl substitution refers to the proportion of all of the hydroxy groups of cellulose located at the 2-, 3-, and 6-positions per glucose unit that are acylated (100% acylation is a degree of substitution of 3).
[0035] Examples of the acyl group include an acetyl group, a propionyl group, a butanoyl group, a heptanoyl group, a hexanoyl group, an octanoyl group, a decanoyl group, a dodecanoyl group, a tridecanoyl group, a tetradecanoyl group, a hexadecanoyl group, an octadecanoyl group, an isobutanoyl group, a tert-butanoyl group, a cyclohexanecarbonyl group, an oleoyl group, a benzoyl group, a naphthylcarbonyl group, a cinnamoyl group, etc. Among these, an acetyl group, a propionyl group, a butanoyl group, a dodecanoyl group, an octadecanoyl group, a tert-butanoyl group, an oleoyl group, a benzoyl group, a naphthylcarbonyl group, a cinnamoyl group, etc. are preferred, and an acetyl group, a propionyl group, a butanoyl group (when the acyl group has 2 to 4 carbon atoms), etc. are particularly preferred.
[0036] Specifically, the cellulose acylate is preferably at least one selected from the group consisting of cellulose (di, tri)acetate, cellulose propionate, cellulose butyrate, cellulose acetate propionate, cellulose acetate butyrate, cellulose acetate phthalate, and cellulose phthalate.
[0037] Among these, cellulose (di-, tri-)acetate, cellulose propionate, cellulose butyrate, cellulose acetate propionate, cellulose acetate butyrate, etc. are preferred, with cellulose diacetate and cellulose acetate propionate being particularly preferred.
[0038] The cellulose diacetate preferably has an average acetylation degree (amount of bound acetic acid) in the range of 51.0% to 56.0%. Examples of commercially available cellulose diacetate include L20, L30, L40, and L50 manufactured by Daicel Corporation, and Ca398-3, Ca398-6, Ca398-10, Ca398-30, and Ca394-60S manufactured by Eastman Chemical Japan Co., Ltd. Examples of commercially available cellulose acetate propionate include CAP-504-0.2, CAP-482-0.5, and CAP-482-20 manufactured by Eastman Chemical Japan Co., Ltd.
[0039] The content of the cellulose acylate (A) in all the curable compounds in the resin composition of the present embodiment is preferably from 5 to 50% by mass, and more preferably from 10 to 40% by mass.
[0040] (Polyfunctional (meth)acrylate (B)) The polyfunctional (meth)acrylate (B) has a function of undergoing photopolymerization and crosslinking reaction upon irradiation with light.
[0041] The polyfunctional (meth)acrylate (B) is not particularly limited as long as it is a compound containing two or more (meth)acryloyloxy groups in one molecule. Among these, (meth)acrylates having from 2 to 10 functionalities are preferred. The polyfunctional (meth)acrylate (B) component may be, for example, a (meth)acrylate having 11 or more functionalities, such as polypentaerythritol poly(meth)acrylate having 11 or more functionalities.
[0042] Examples of bifunctional (meth)acrylates include dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, propylene oxide modified neopentyl glycol di(meth)acrylate, neopentyl glycol adipate di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, and caprolactone. Examples of the di(meth)acrylate include modified dicyclopentenyl di(meth)acrylate, polyethylene glycol di(meth)acrylate, modified bisphenol A di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, ethylene oxide modified phosphate di(meth)acrylate, allylated cyclohexyl di(meth)acrylate, isocyanurate di(meth)acrylate, pentaerythritol di(meth)acrylate, dipentaerythritol di(meth)acrylate, tripentaerythritol di(meth)acrylate, and tetrapentaerythritol di(meth)acrylate.
[0043] Examples of trifunctional (meth)acrylates include pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, tripentaerythritol tri(meth)acrylate, tetrapentaerythritol tri(meth)acrylate, propionic acid-modified dipentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxy tri(meth)acrylate, ethylene oxide-modified trimethylolpropane tri(meth)acrylate, propylene oxide-modified trimethylolpropane tri(meth)acrylate, polyether tri(meth)acrylate, glycerin propoxy tri(meth)acrylate, and tris(acryloxyethyl)isocyanurate.
[0044] Examples of tetrafunctional (meth)acrylates include pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, tripentaerythritol tetra(meth)acrylate, tetrapentaerythritol tetra(meth)acrylate, pentaerythritol ethoxy tetra(meth)acrylate, and ditrimethylolpropane tetra(meth)acrylate.
[0045] Examples of the pentafunctional (meth)acrylate include dipentaerythritol penta(meth)acrylate, tripentaerythritol penta(meth)acrylate, tetrapentaerythritol penta(meth)acrylate, propionic acid-modified dipentaerythritol penta(meth)acrylate, and dipentaerythritol monohydroxypenta(meth)acrylate.
[0046] Examples of hexafunctional (meth)acrylates include dipentaerythritol hexa(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tetrapentaerythritol hexa(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate.
[0047] Examples of the heptafunctional (meth)acrylate include tripentaerythritol hepta(meth)acrylate and tetrapentaerythritol hepta(meth)acrylate.
[0048] Examples of the octafunctional (meth)acrylate include tripentaerythritol octa(meth)acrylate and tetrapentaerythritol octa(meth)acrylate.
[0049] An example of the nona-functional (meth)acrylate is tetrapentaerythritol nona(meth)acrylate.
[0050] An example of the decafunctional (meth)acrylate is tetrapentaerythritol deca(meth)acrylate.
[0051] Among these, dipentaerythritol polyacrylate, tricyclodecane dimethanol diacrylate, and trimethylolpropane triacrylate are preferable.
[0052] Moreover, as the compound containing two or more (meth)acryloyloxy groups in one molecule, urethane (meth)acrylate, polyester (meth)acrylate, etc. may be used.
[0053] The urethane (meth)acrylate is not particularly limited. For example, it may be a monomer or oligomer obtained by reacting a diisocyanate, a polyol, and a (meth)acrylate compound having a hydroxyl group. In addition, as the urethane (meth)acrylate, for example, it may be the urethane (meth)acrylate described in JP-A-2002-265650, JP-A-2002-355936, JP-A-2002-067238, etc.
[0054] Examples of diisocyanates include TDI, MDI, HDI, IPDI, and HMDI.
[0055] Examples of polyols include poly(propylene oxide) diol, poly(tetramethylene oxide) diol, ethoxylated bisphenol A, ethoxylated bisphenol S spiroglycol, caprolactone-modified diol, and carbonate diol.
[0056] Examples of the (meth)acrylate compound having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, glycidol di(meth)acrylate, and pentaerythritol triacrylate.
[0057] Specific examples of the urethane (meth)acrylate include, but are not limited to, an adduct of TDI and hydroxyethyl acrylate, an adduct of IPDI and hydroxyethyl acrylate, an adduct of HDI and pentaerythritol triacrylate (PETA), a compound obtained by reacting the remaining isocyanate with dodecyloxyhydroxypropyl acrylate after preparing an adduct of TDI and PETA, an adduct of 6,6 nylon and TDI, and an adduct of pentaerythritol, TDI, and hydroxyethyl acrylate.
[0058] Polyester (meth)acrylate is an acrylate obtained by condensing (meth)acrylic acid with the hydroxyl group remaining in the polyester skeleton synthesized from polyol and dibasic acid.
[0059] Specific polyester acrylates are not particularly limited, and examples thereof include a reaction product of phthalic anhydride / propionoxide / acrylic acid, a reaction product of adipic acid / 1,6-hexanediol / acrylic acid, and a reaction product of trimellitic acid / diethylene glycol / acrylic acid.
[0060] It is preferable that the polyfunctional (meth)acrylate (B) component further contains a hydroxyl group. It is presumed that this is because, during the polymerization and crosslinking reaction between the cellulose acylate (A) and the crosslinking agent (C), the polymerization and crosslinking reaction between the cellulose acylate (A) component, the polyfunctional (meth)acrylate (B) or its (co)polymer, and the crosslinking agent (C) proceeds.
[0061] The hydroxyl value of the polyfunctional (meth)acrylate (B) is not particularly limited, but is preferably 100 mg KOH / g or less. The hydroxyl value of the polyfunctional (meth)acrylate (B) is more preferably 50 mg KOH / g or less. When the hydroxyl value is within the above range, the protective layer made of the cured product of the resin composition of the present embodiment and the polarizing plate having the same become more suitable, and the scratch resistance and durability of the polarizing plate become good. It is presumed that this is because the progress of the polymerization and crosslinking reaction between the polyfunctional (meth)acrylate (B) or its (co)polymer and the crosslinking agent (C) becomes an appropriate range, and the polymerization and crosslinking reaction between the cellulose acylate (A) and the crosslinking agent (C) component proceeds more smoothly. The hydroxyl value can be determined by a measurement in accordance with JIS K0070:1992.
[0062] The polyfunctional (meth)acrylate (B) may be a synthetic product or a commercially available product. Examples of commercially available products include A-TMPT, A-TMM-3, A-TMM-3L, A-TMM-3LM-N, ATM-35E, A-TMMT, A-9550, and A-DPH manufactured by Shin-Nakamura Chemical Co., Ltd., ARONIX (registered trademark) M-305, M-402, and M-405 manufactured by Toagosei Co., Ltd., and Viscoat (registered trademark) #295, TMPTA, #802, and TriPEA manufactured by Osaka Organic Chemical Industry Co., Ltd.
[0063] The polyfunctional (meth)acrylate (B) may be used alone or in combination of two or more kinds.
[0064] In the resin composition of the present embodiment, the content of the polyfunctional (meth)acrylate (B) is 100 parts by mass or more and 1000 parts by mass or less, and preferably 100 parts by mass or more and 500 parts by mass or less, relative to 100 parts by mass of the cellulose acylate (A). If the content of the polyfunctional (meth)acrylate (B) is less than 100 parts by mass, the scratch resistance of the cured product of the resin composition decreases, and the change rate of the total light transmittance and the change rate of the polarization degree of the polarizing plate having the cured product of the resin composition as a protective layer by exposure to a moist and hot environment increases. If the content of the polyfunctional (meth)acrylate (B) exceeds 1000 parts by mass, the adhesion and flexibility of the cured product of the resin composition decrease.
[0065] (Crosslinking agent (C)) The crosslinking agent (C) preferably has two or more isocyanate groups in one molecule, and more preferably has two or more isocyanate groups and one or more acrylate groups in one molecule. The crosslinking agent having two or more isocyanate groups in one molecule is not particularly limited as long as it can promote polymerization and crosslinking reaction with cellulose acylate (A). For example, an isocyanate crosslinking agent, a carbodiimide crosslinking agent, an oxazoline crosslinking agent, an epoxy crosslinking agent, an aziridine crosslinking agent, a peroxide, etc. can be mentioned. Here, the peroxide means a compound having a peroxide structure "-OO-" in the molecular structure. These may be used alone or in combination of two or more. When two or more types are used, two or more types of the same system may be combined, or one or more types of different systems may be combined.
[0066] The isocyanate-based crosslinking agent is not particularly limited, and a known compound having an isocyanate group (isocyanate compound) can be used. Examples of the compound having an isocyanate group include monofunctional isocyanates and polyfunctional isocyanates. Among these, polyfunctional isocyanates are preferred. Examples of the polyfunctional isocyanates include bifunctional isocyanates (compounds having two isocyanate groups) and trifunctional or higher isocyanates (compounds having three or more isocyanate groups).
[0067] Examples of bifunctional isocyanates include aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, carbodiimide-modified diisocyanates of these diisocyanates, and polymer compounds having these diisocyanates at the main chain end, side chain, or side chain end.
[0068] Examples of the aliphatic diisocyanates include 1,5-pentamethylene diisocyanate, 1,6-hexamethylene diisocyanate (HDI), trimethylhexamethylene diisocyanate (TMHDI), lysine diisocyanate, and norbornane diisocyanate methyl (NBDI).
[0069] Examples of alicyclic diisocyanates include transcyclohexane-1,4-diisocyanate, isophorone diisocyanate (IPDI), H6-XDI (hydrogenated XDI), and H12-MDI (hydrogenated MDI).
[0070] Examples of aromatic diisocyanates include dimer acid diisocyanate, 2,4-tolylene diisocyanate (2,4-TDI), 2,6-tolylene diisocyanate (2,6-TDI), 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4'-diphenylmethane diisocyanate (2,4'-MDI), 1,4-phenylene diisocyanate, xylylene diisocyanate (XDI), tetramethylxylidene diisocyanate (TMXDI), tolidine diisocyanate (TODI), and 1,5-naphthalene diisocyanate (NDI).
[0071] Examples of the tri- or higher functional isocyanate include an isocyanurate-modified product obtained by polycondensing the bifunctional isocyanate, an adduct-modified product obtained by adduct-modifying the bifunctional isocyanate, a biuret-modified product obtained by biuret-modifying the bifunctional isocyanate with a trihydric alcohol such as glycerin or trimethylolpropane, and a polymer compound having the bifunctional isocyanate or an adduct, biuret or isocyanurate thereof at the main chain end, side chain or side chain end.
[0072] The carbodiimide crosslinking agent is not particularly limited, and any known carbodiimide compound can be used. Examples of the carbodiimide compound include high molecular weight polycarbodiimides produced by decarboxylation condensation reaction of diisocyanate in the presence of a carbodiimide catalyst. Examples of diisocyanates used in the decarboxylation condensation reaction include 4,4'-diphenylmethane diisocyanate, 3,3'-dimethoxy-4,4'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, 4,4'-diphenylether diisocyanate, 3,3'-dimethyl-4,4'-diphenylether diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 1-methoxyphenyl-2,4-diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and tetramethylxylylene diisocyanate. Examples of the carbodiimide catalyst used in the decarboxylation condensation reaction include phospholene oxides such as 1-phenyl-2-phospholene-1-oxide, 3-methyl-2-phospholene-1-oxide, 1-ethyl-3-methyl-2-phospholene-1-oxide, 1-ethyl-2-phospholene-1-oxide, and 3-phospholene isomers thereof.
[0073] The oxazoline crosslinking agent is not particularly limited, and a known oxazoline compound can be used. Examples of the oxazoline compound include oxazoline group-containing polymers. Specific examples of the oxazoline compound include oxazoline group-containing acrylic polymers and oxazoline group-containing acrylic / styrene polymers. Here, examples of the oxazoline group-containing acrylic polymers include oxazoline group-containing acrylic polymers that include a main chain made of an acrylic skeleton and have oxazoline groups on the side chains of the main chain. Examples of the oxazoline group-containing acrylic / styrene polymers include oxazoline group-containing acrylic / styrene polymers that include a main chain made of an acrylic skeleton or a styrene skeleton and have oxazoline groups on the side chains of the main chain. Examples of the oxazoline group include a 2-oxazoline group, a 3-oxazoline group, and a 4-oxazoline group.
[0074] The epoxy crosslinking agent is not particularly limited, and a known epoxy compound can be used. Examples of the epoxy compound include liquid epoxy compounds. Liquid epoxy compounds are preferred in that they facilitate the mixing operation when producing the pressure-sensitive adhesive composition.
[0075] The aziridine crosslinking agent is not particularly limited, and a known aziridine compound can be used. Examples of the aziridine compound include polyfunctional aziridine compounds having multiple aziridine rings. Examples of the polyfunctional aziridine compound include compounds disclosed in U.S. Pat. No. 3,225,013, U.S. Pat. No. 4,490,505, and U.S. Pat. No. 5,534,391, and JP-A No. 2003-104970. Examples of the polyfunctional aziridine compound include trifunctional aziridine compounds (compounds having three aziridine rings). Examples of trifunctional aziridine compounds include trimethylolpropane tris[3-aziridinyl propionate], trimethylolpropane tris[3-(2-methyl-aziridinyl)-propionate], trimethylolpropane tris[2-aziridinyl butyrate], pentaerythritol tris-3-(1-aziridinyl propionate), and pentaerythritol tetrakis-3-(1-aziridinyl propionate).
[0076] The peroxide is not particularly limited, and known peroxides can be used. Examples of the peroxide include diisopropyl peroxydicarbonate, bis(2-ethylhexyl) peroxydicarbonate, bis(4-t-butylcyclohexyl) peroxydicarbonate (also known as bis(4-t-butylcyclohexyl) peroxydicarbonate), bis-sec-butyl peroxydicarbonate, t-butyl peroxyneodecanoate, t-hexyl peroxypivalate, t-butyl peroxypivalate, dilauroyl peroxide, bis-n-octanoyl peroxide, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, bis(4-methylbenzoyl) peroxide, dibenzoyl peroxide (benzoyl peroxide), and t-butyl peroxybutyrate.
[0077] Among these, isocyanate-based crosslinking agents are preferred.
[0078] As the isocyanate-based crosslinking agent, hexamethylene diisocyanate (HDI) or pentamethylene diisocyanate (PDI), their adducts, biuret or isocyanurates, or polymer compounds having them at the main chain end, side chain or side chain end are preferred. As the isocyanate-based crosslinking agent, an adduct or isocyanurate of hexamethylene diisocyanate (HDI) or pentamethylene diisocyanate (PDI) is more preferred. Alternatively, a polymer compound obtained by a condensation reaction of hexamethylene diisocyanate (HDI) or pentamethylene diisocyanate (PDI) with a diol is more preferred. Here, as the hexamethylene diisocyanate (HDI), for example, 1,6-hexamethylene diisocyanate and the like can be mentioned. Examples of pentamethylene diisocyanates (PDIs) include 1,5-pentamethylene diisocyanate, etc. These isocyanate crosslinking agents can more efficiently promote polymerization and crosslinking reactions with the component (A).
[0079] The crosslinking agent (C) may be a synthetic product or a commercially available product. Examples of commercially available products include isocyanate-based crosslinking agents such as Laromer PR9000 manufactured by BASF, Coronate (registered trademark) L (e.g., L-45E, etc.), HL, HX, 2030, and 2031 manufactured by Tosoh Corporation, Takenate (registered trademark) D-102, D-110N, D-200, and D-202 manufactured by Mitsui Chemicals, and Duranate (registered trademark) 24A-100 and TPA-10 manufactured by Asahi Kasei Chemicals. Examples of the carbodiimide crosslinking agent include Carbodilite V-01, V-03, V-05, V-07, V-09, etc. Examples of the carbodiimide crosslinking agent include Carbodilite V-01, V-03, V-05, V-07, V-09, etc., manufactured by Nisshinbo Chemical Co., Ltd. Examples of the carbodiimide crosslinking agent include Carbodilite V-01, V-03, V-05, V-07, V-09, etc., manufactured by Nisshinbo Chemical Co., Ltd. Examples of oxazoline-based crosslinking agents include EPOCROS (registered trademark) WS-300, WS-500, WS-700, K-1000 series, and K-2000 series manufactured by Nippon Shokubai Co., Ltd. Examples of epoxy-based crosslinking agents include TETRAD-C and TETRAD-X manufactured by Mitsubishi Gas Chemical Company, Inc., ADEKA Resin EPU series and EPR series manufactured by ADEKA Corporation, and CELLOXIDE series manufactured by Daicel Corporation. Examples of aziridine-based crosslinking agents include Chemitite (registered trademark) PZ-33 and DZ-22E manufactured by Nippon Shokubai Co., Ltd. Examples of peroxides include Percumyl (registered trademark) ND, Perloyl (registered trademark) IB, NPP, IPP, SBP, TCP, OPP, 355, L, SA, Perocta (registered trademark) ND, O, Perhexyl (registered trademark) ND, PV, O, I, Perbutyl (registered trademark) ND, NHP, PV, O, L, I, A, Perhexa (registered trademark) 25O, MC, TMH, HC, C, 25Z, 22, Niper (registered trademark) PMB, BMT, BW, BMT-K40, BMT-M, and Pertetra (registered trademark) A, all of which are manufactured by NOF Corporation.
[0080] The crosslinking agent (C) may be used alone or in combination of two or more kinds.
[0081] The content (mass%) of isocyanate groups in the crosslinking agent (C) is preferably 0.1 to 5 times, more preferably 0.5 to 5 times, the content (mass%) of hydroxyl groups in the cellulose acylate (A). If the content of isocyanate groups is 0.1 times or more the content of hydroxyl groups in the cellulose acylate (A), a crosslinking effect is obtained, and the durability and scratch resistance of the cured product of the resin composition are improved. If the content of isocyanate groups is 5 times or less the amount of hydroxyl groups in the cellulose acylate (A), the stability of the resin liquid contained in the resin composition is obtained. The hydroxyl group content can be calculated by the following formula (1). Hydroxyl content = (17 / hydroxyl equivalent) x 100 (1) In the above formula (1), 17 represents the mass of 1 mole of hydroxyl groups. The hydroxyl group equivalent is the molecular weight per hydroxyl group and is calculated by the following formula (2). Hydroxyl equivalent = (56.1 x 1000) / hydroxyl value (2) In the above formula (2), 56.1 represents the molecular weight of KOH. The isocyanate group content can be calculated by the following formula (3). Isocyanate group content = (42 / amine equivalent) x 100 (3) In the above formula (3), 42 represents the mass of 1 mole of isocyanate groups. The amine equivalent represents the molecular weight per one isocyanate group.
[0082] (Photoradical initiator (D)) The photoradical initiator (D) is not particularly limited, and a known one can be used. Examples of the photoradical initiator (D) include acetophenone compounds, benzoin compounds, benzophenone compounds, thioxanthone compounds, anthraquinone compounds, acylphosphine oxide compounds, etc. In addition, 3,3',4,4'-tetra(t-butyloperoxycarbonyl)benzophenone, acrylated benzophenone, etc. can also be mentioned.
[0083] Examples of acetophenone compounds include 4-phenoxydichloroacetophenone, diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 1-hydroxycyclohexyl phenyl ketone, 4-(2-hydroxyethoxy)-phenyl(2-hydroxy-2-propyl)ketone, 2-methyl-[4-(methylthio)phenyl]-2-morpholino-1-propanone, and 2,2-dimethoxy-2-phenylacetophenone.
[0084] Examples of the benzoin compound include benzoin, benzoin methyl ether, benzoin isoethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.
[0085] Examples of the benzophenone compound include benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, and 3,3'-dimethyl-4-methoxybenzophenone.
[0086] Examples of thioxanthone compounds include thioxanthone, 2-chlorothioxanthone, 2,4-dichlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, isopropylthioxanthone, and 2,4-diisopropylthioxanthone.
[0087] Examples of anthraquinone compounds include 4,4'-dimethylaminothioxanthone (also known as mineral's ketone), 4,4'-diethylaminobenzophenone, α-acyloxime ester, benzil, methylbenzoyl formate, and 2-ethylanthraquinone.
[0088] Examples of the acylphosphine oxide compound include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and the like.
[0089] Examples of the acrylated benzophenone include 3,3',4,4'-tetra(t-butyloperoxycarbonyl)benzophenone, acrylated benzophenone, and the like.
[0090] The photoradical initiator (D) may be a synthetic product or a commercially available product. Examples of commercially available products include Omnirad (registered trademark) 127, 184, 369, 651, 819, 907, 1173, and TPO H manufactured by IGM RESINS, Esacure (registered trademark) KIP150 and TZT manufactured by DKSH Japan Co., Ltd., and KAYACURE (registered trademark) BMS and DMBI manufactured by Nippon Kayaku Co., Ltd. These photoradical initiators (D) may be used alone or in combination of two or more.
[0091] In the resin composition of this embodiment, the content of the photoradical initiator (D) is preferably 0.1 parts by mass or more and 50 parts by mass or less, and more preferably 5 parts by mass or more and 40 parts by mass or less, relative to 100 parts by mass of the cellulose acylate (A). If the content of the photoradical initiator (D) is 0.1 parts by mass or more, the resin composition is sufficiently cured. If the content of the photoradical initiator (D) is 50 parts by mass or less, the cured product of the resin composition has excellent scratch resistance.
[0092] (Ultraviolet absorber (E)) The resin composition of the present embodiment may contain an ultraviolet absorber (E). Examples of the ultraviolet absorber (E) include 2-(2H-benzotriazol-2-yl)-p-cresol, 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol, 2-(2H-benzotriazol-2-yl)-4,6-di-(tert-pentyl)phenol, 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol, and 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol]. Reaction products of 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate with polyethylene glycol 300, 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol, 2,2-bis{[2-cyano-3,3-diphenylacryloyloxy]methyl}propane-1,3-diyl-bis(2-cyano-3,3-diphenylacrylate), ethyl 2-cyano-3,3-diphenylacrylate, 2-ethylhexyl 2-cyano-3,3-diphenylacrylate, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-(hexyloxy)-phenol, octabenzone, 2,2' -Dihydroxy-4,4'-dimethoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2-ethylhexyl-4-methoxycinnamate, 2,4-di-tert-butylphenyl-3,5-di-tert-butyl-4-hydroxybenzoate and the like are exemplified, for example, ADK STAB LA-31, ADK STAB LA-32, ADK STAB LA-36, ADK STAB LA-29, ADK STAB LA-46, ADK STAB LA-F70, ADK STAB 1413 (all manufactured by ADEKA CORPORATION), Tinuvin P, Tinuvin 234, Tinuvin 326, Tinuvin 328, Tinuvin 329, Tinuvin 360, Tinuvin 213, Tinuvin 571, Uvinul 3030, Uvinul 3035, Uvinul 3039, Tinuvin B 75, Tinuvin PUR 866, Tinuvin 1577 ED, Chimassorb 81, Uvinul 3049, Uvinul Commercially available products such as Uvinul 3050, Uvinul 3088, and Tinuvin 20 (all manufactured by BASF) can be used. These ultraviolet absorbents may be used alone or in combination of two or more.
[0093] In the resin composition of the present embodiment, the content of the ultraviolet absorber (E) is preferably 0.1 parts by mass or more and 35 parts by mass or less with respect to 100 parts by mass of the cellulose acylate (A). If the content of the ultraviolet absorber (E) is 0.1 parts by mass or more, the cured product of the resin composition is less likely to deteriorate due to ultraviolet rays. If the content of the ultraviolet absorber (E) is 35 parts by mass or less, the cured product of the resin composition has excellent scratch resistance.
[0094] The resin composition of the present embodiment may contain a leveling agent, a defoaming agent, and the like in addition to the above components.
[0095] The resin composition of this embodiment is obtained by adding predetermined amounts of cellulose acylate (A), polyfunctional (meth)acrylate (B), crosslinking agent (C), photoradical initiator (D), and, if necessary, ultraviolet absorber (E) and solvent, and stirring and mixing them.
[0096] The resin composition according to the present embodiment described above contains cellulose acylate (A), polyfunctional (meth)acrylate (B), crosslinking agent (C), and photoradical initiator (D), and therefore can form a cured product that is excellent in abrasion resistance and bending resistance and can be used as a protective layer for a polarizer.
[0097] [Cured product] A cured product according to one embodiment of the present invention will now be described. The cured product of this embodiment is a cured product of the resin composition of this embodiment. The cured product of this embodiment can be obtained by applying the resin composition of this embodiment to the surface of an object (subject to be coated) and then curing the resin composition.
[0098] The method for applying the resin composition is not particularly limited, and for example, a doctor blade, a wire bar, a die coater, a gravure coater, etc. may be used. When applying the resin composition, the viscosity of the resin composition may be adjusted using a solvent.
[0099] The coating film made of the resin composition is cured by irradiating it with active energy rays to form a protective film. Examples of active energy rays include ultraviolet rays, visible light, electron beams, and X-rays. Among these, ultraviolet rays are preferably used. Examples of sources of ultraviolet rays include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, chemical lamps, xenon lamps, black light lamps, and metal halide lamps.
[0100] The cured product of the present embodiment has a transmittance of 10% or less, preferably 6% or less, for light having a wavelength of 380 nm. If the transmittance of light having a wavelength of 380 nm is 10% or less, the product has the same level of ultraviolet absorption as a protective film, and when the cured product of the resin composition is used as a protective film for a polarizing plate, the incidence of ultraviolet rays on a polarizer or the like can be suppressed. The transmittance of the cured product at a wavelength of 380 nm is measured as follows. The cured product of the resin composition formed on the release film is peeled off from the release film, and the spectral transmittance of the single layer of the cured product is measured. At this time, the thickness of the cured product is set to 15 μm. For example, an ultraviolet-visible spectrophotometer (model: UV-2550, manufactured by Shimadzu Corporation) is used to measure the spectral transmittance of the cured product.
[0101] The thickness of the cured product is preferably 25 μm or less. When the cured product of the resin composition is used as a protective film for a polarizing plate, the thickness of the polarizing plate can be reduced.
[0102] The cured product according to the present embodiment described above is a cured product of the resin composition of the present embodiment, and has a transmittance of 10% or less at a wavelength of 380 nm. Therefore, it is possible to form a cured product that has excellent scratch resistance and bending resistance and can be used as a protective layer for a polarizer.
[0103] [Polarizing plate] A polarizing plate according to one embodiment of the present invention will be described. The polarizing plate of the present embodiment includes a polarizer and a protective layer provided on at least one surface of the polarizer, and the protective layer is made of the cured product of the present embodiment. That is, the polarizing plate of the present embodiment is a laminate having a polarizer and a protective layer.
[0104] An example of a polarizer is a dyed and stretched polyvinyl alcohol film.
[0105] The thickness of the protective layer is preferably 25 μm or less, and more preferably 20 μm or less. Whether the protective layer is provided on one side of the polarizer or on both sides of the polarizer, the thickness of the protective layer is preferably within the above range. If the thickness of the protective layer is 25 μm or less, the polarizing plate has excellent bending resistance. In addition, in consideration of the function (durability, etc.) of the protective layer as a polarizer protective layer, the thickness of the protective layer is preferably 5 μm or more.
[0106] As a method for forming a protective layer on at least one surface of the polarizer, a method similar to the method for forming a cured product made of the resin composition of the present embodiment described above can be used.
[0107] The polarizing plate according to the present embodiment includes a polarizer and a protective layer provided on at least one surface of the polarizer, the protective layer being made of the cured product according to the present embodiment, and therefore a polarizing plate having excellent scratch resistance and bending resistance can be obtained.
[0108] [Image display device] An image display device according to an embodiment of the present invention will be described. The image display device of this embodiment includes an image display element and polarizing plates provided on one surface and the other surface of the image display element, the polarizing plates being the polarizing plates of this embodiment.
[0109] Examples of the image display device of this embodiment include a liquid crystal display (LCD), an organic electroluminescence display (OLED), etc. Examples of the image display element include a liquid crystal display element, an organic EL element, etc.
[0110] The image display device according to the present embodiment includes an image display element and polarizing plates provided on one surface and the other surface of the image display element, the polarizing plates being the polarizing plates of the present embodiment, and therefore an image display device having excellent scratch resistance and bending resistance can be obtained. EXAMPLES
[0111] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0112] [Synthesis example] Cellulose acetate (product name: L-20, manufactured by Daicel Chemical Industries, Ltd.) was dried in a vacuum dryer to adjust the moisture content in the cellulose acetate to 0.8% by mass. The hydroxyl value of the dried cellulose acetate was 97.2 mgKOH / g. 100 parts by mass of dried cellulose acetate was dissolved in methyl ethyl ketone to a concentration of 10% by mass, to prepare a methyl ethyl ketone solution of cellulose acetate. The methyl ethyl ketone solution was heated to 70°C. After the temperature of the methyl ethyl ketone solution reached 70° C., 13.1 parts by mass of isocyanate acrylate (2-acryloyloxyethyl isocyanate, product name: AOI-VM, manufactured by Showa Denko KK) was added to the methyl ethyl ketone solution. Two hours after the isocyanate acrylate was added to the methyl ethyl ketone solution, 0.15 parts by mass of dibutyltin dilaurate was further added to the mixture of the methyl ethyl ketone solution and the isocyanate acrylate, and the mixture was stirred to continue the reaction. Thereafter, aging was carried out, and when the isocyanate concentration reached 0.1% by mass or less, the reaction liquid was cooled to room temperature to obtain a solution containing a cellulose derivative in which the hydroxyl groups of cellulose acetate were substituted with groups containing acryloyl groups.
[0113] [Example 1] (Preparation of resin composition) As shown in Table 1, 100 parts by mass of a cellulose polymer (cellulose acetate propionate, trade name: CAP-504-02, manufactured by Eastman Co.), 26.2 parts by mass of a crosslinking agent (trade name: Duranate (registered trademark) 24A-100, manufactured by Asahi Kasei Co.), 100 parts by mass of a multifunctional acrylate (dipentaerythritol polyacrylate, trade name: A9550, manufactured by Shin-Nakamura Chemical Co., Ltd.), and 10 parts by mass of a photoradical initiator (2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropynyl)benzyl)phenyl)-2-methylpropan-1-one (trade name: Omnirad 127, manufactured by IGM Resins BV)) were mixed to obtain a resin composition of Example 1.
[0114] (Preparation of cured product) In the resin composition of Example 1, the content (mass %) of the isocyanate group in the crosslinking agent was 0.5 times the content (mass %) of the hydroxyl group in the cellulose polymer. The resin composition of Example 1 was diluted with methyl ethyl ketone to a solid content concentration of 40 mass %, and the diluted solution was applied to one side of a PET film (product name: Peelable PET SP3030, manufactured by Toyo Cross Co., Ltd.) using an applicator, followed by drying at 120°C for 5 minutes to form a coating film on one side of the PET film. Next, the coating was irradiated with a small UV irradiator (model: ECS-401GX, metal halide lamp, manufactured by iGraphics Co., Ltd.) with an integrated light dose of 1000 mJ / cm 2 The resin composition of Example 1 was cured and the cured product (cured film) was formed on one surface of the PET film.
[0115] (Preparation of polarizer) A polyvinyl alcohol film having a thickness of 45 μm and made of polyvinyl alcohol with an average degree of polymerization of 2400 and a degree of saponification of 99.9% was immersed in warm water at 28° C. for 90 seconds to cause it to swell. Next, the swollen polyvinyl alcohol film was immersed in an aqueous solution of iodine / potassium iodide (mass ratio 2 / 3) with a concentration of 0.6% by mass, and the polyvinyl alcohol film was dyed while being stretched 2.1 times. Thereafter, the polyvinyl alcohol film was stretched in an aqueous boric acid ester solution at 60° C. to a total stretch ratio of 5.8 times. The stretched polyvinyl alcohol film was washed with water and then dried at 45° C. for 3 minutes to obtain a polarizer (thickness: 12 μm).
[0116] (Preparation of Adhesive Composition) An aqueous solution was prepared by diluting an acetoacetyl-modified polyvinyl alcohol resin (product name: Gohsefimer (registered trademark) ZZ-200, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) with water to a solid content concentration of 3 mass %. A curing agent (product name: Safelinker SPM-01, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) adjusted to an active ingredient content of 10% by mass was mixed into the aqueous solution to obtain an adhesive composition solution. In the obtained adhesive composition solution, the content of the curing agent was 5 parts by mass based on 100 parts by mass of the acetoacetyl-modified polyvinyl alcohol resin.
[0117] (Preparation of polarizing plate) A polarizing plate was produced as shown in Figure 1. Figure 1 is a schematic diagram showing an example of a method for producing a polarizing plate. The arrow in Figure 1 indicates the direction in which the film is moved. 1, a polarizer 30 was sandwiched between a release film 10 with a protective layer and a triacetyl cellulose (TAC) film 20, and an appropriate amount of adhesive composition solution 40 was dropped with a dropper onto both sides of the polarizer 30 (side 30a facing the release film 10 with a protective layer and side 30b facing the TAC film 20). The release film 10 with a protective layer had a release film and a protective layer formed on one side of the release film and made of a cured product of the resin composition of Example 1. Next, a pair of rollers 100, 100 sandwiched the laminate of the protective layer-attached release film 10, the TAC film 20, the polarizer 30 and the adhesive composition solution 40, and the protective layer-attached release film 10 and the polarizer 30 were bonded together via the adhesive composition solution 40, and the TAC film 20 and the polarizer 30 were bonded together to obtain a pre-dried polarizing plate 50. A surface 10a of the protective layer-attached release film 10 facing the polarizer 30 has been subjected to a corona treatment. The surface 10a of the protective layer-attached release film 10 is the surface on the protective layer side. A surface 20a of the TAC film 20 facing the polarizer 30 has been subjected to a saponification treatment. The obtained pre-dried polarizing plate 50 was dried at 70° C. for 5 minutes to obtain a polarizing plate having a protective layer-attached release film 10, an adhesive layer, a polarizer 30, an adhesive layer and a TAC film 20 laminated in this order.
[0118] [Example 2] A resin composition of Example 2 was prepared in the same manner as in Example 1, except that the blending amounts of each component were as shown in Table 1. In the resin composition of Example 2, the content (mass %) of the isocyanate group in the crosslinking agent relative to the content (mass %) of the hydroxyl group in the cellulose polymer was 0.1 times. In addition, in the same manner as in Example 1, a cured product (cured film) made of the resin composition of Example 2 was formed to a thickness of 15 μm.
[0119] [Example 3] A resin composition of Example 3 was prepared in the same manner as in Example 1, except that the blending amounts of each component were as shown in Table 1. In the resin composition of Example 3, the content (mass %) of the isocyanate group in the crosslinking agent was 0.5 times the content (mass %) of the hydroxyl group in the cellulose polymer. In addition, in the same manner as in Example 1, a cured product (cured film) made of the resin composition of Example 3 was formed to a thickness of 15 μm.
[0120] [Example 4] The resin composition of Example 4 was prepared in the same manner as in Example 1, except that dipentaerythritol polyacrylate (product name: A9550, manufactured by Shin-Nakamura Chemical Co., Ltd.) and 10-functional fatty acid urethane acrylate (manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) were used as the multifunctional acrylate, and the blending amounts of each component were as shown in Table 1. In the resin composition of Example 4, the content (mass %) of the isocyanate group in the crosslinking agent was 0.7 times the content (mass %) of the hydroxyl group in the cellulose polymer. In addition, in the same manner as in Example 1, a cured product (cured film) made of the resin composition of Example 4 was formed to a thickness of 15 μm.
[0121] [Example 5] The resin composition of Example 5 was prepared in the same manner as in Example 1, except that cellulose acetate (product name: CA-398-3, manufactured by Eastman Co.) was used as the cellulose polymer, trimethylpropane acrylate (product name: Viscoat #295, manufactured by Osaka Organic Chemical Industry Co., Ltd.) was used as the polyfunctional acrylate, and the amounts of each component were as shown in Table 1. In the resin composition of Example 5, the content (mass %) of the isocyanate group in the crosslinking agent was 0.3 times the content (mass %) of the hydroxyl group in the cellulose polymer. In addition, in the same manner as in Example 1, a cured product (cured film) made of the resin composition of Example 5 was formed to a thickness of 15 μm.
[0122] [Example 6] A resin composition of Example 6 was prepared in the same manner as in Example 5, except that the blending amounts of each component were as shown in Table 1. In the resin composition of Example 6, the content (mass %) of the isocyanate group in the crosslinking agent was 0.5 times the content (mass %) of the hydroxyl group in the cellulose polymer. In addition, in the same manner as in Example 1, a cured product (cured film) made of the resin composition of Example 6 was formed to a thickness of 15 μm.
[0123] [Example 7] A resin composition of Example 7 was prepared in the same manner as in Example 5, except that the blending amounts of each component were as shown in Table 1. In the resin composition of Example 7, the content (mass %) of the isocyanate group in the crosslinking agent was 0.7 times the content (mass %) of the hydroxyl group in the cellulose polymer. Furthermore, in the same manner as in Example 1, a cured product (cured film) made of the resin composition of Example 7 was formed to a thickness of 15 μm.
[0124] [Example 8] As a crosslinking agent, a polymer of 2-hydroxyethyl acrylate (HEA) and 1,6-diisocyanatohexane (HDI) (trade name: Laromer PR9000, manufactured by BASF) was used, as a photoradical initiator, 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropynyl)benzyl)phenyl)-2-methylpropan-1-one (trade name: Omnirad 127, manufactured by IGM Resins BV) and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (trade name: Omnirad TPO H, manufactured by IGM Resins BV) were used, and an ultraviolet absorber (trade name: Uvinul (registered trademark) 3050, manufactured by BASF) was added. The resin composition of Example 8 was prepared in the same manner as in Example 1, except that the amounts of each component were as shown in Table 2. In the resin composition of Example 8, the content (mass %) of the isocyanate group in the crosslinking agent was 0.7 times the content (mass %) of the hydroxyl group in the cellulose polymer. Furthermore, in the same manner as in Example 1, a cured product (cured film) made of the resin composition of Example 8 was formed to a thickness of 15 μm.
[0125] [Example 9] The resin composition of Example 9 was prepared in the same manner as in Example 8, except that dipentaerythritol polyacrylate (product name: A9550, manufactured by Shin-Nakamura Chemical Co., Ltd.) and trimethylpropane acrylate (product name: Viscoat #295, manufactured by Osaka Organic Chemical Industry Co., Ltd.) were used as the multifunctional acrylate, and the amounts of each component were as shown in Table 2. In the resin composition of Example 9, the content (mass %) of the isocyanate group in the crosslinking agent relative to the content (mass %) of the hydroxyl group in the cellulose polymer was 1.0 times. Furthermore, in the same manner as in Example 1, a cured product (cured film) made of the resin composition of Example 9 was formed to a thickness of 15 μm.
[0126] [Example 10] The resin composition of Example 10 was prepared in the same manner as in Example 9, except that Asahi Kasei Corporation's Duranate (registered trademark) 24A-100 was used as the crosslinking agent and the amounts of each component were as shown in Table 2. In the resin composition of Example 10, the content (mass %) of the isocyanate group in the crosslinking agent relative to the content (mass %) of the hydroxyl group in the cellulose polymer was 1.0 times. In addition, in the same manner as in Example 1, a cured product (cured film) made of the resin composition of Example 10 was formed to a thickness of 15 μm.
[0127] [Example 11] The resin composition of Example 11 was prepared in the same manner as in Example 8, except that dipentaerythritol polyacrylate (product name: A9550, manufactured by Shin-Nakamura Chemical Co., Ltd.), tricyclodecane dimethanol diacrylate (product name: A-DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.), and 10-functional fatty acid urethane acrylate (manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) were used as the multifunctional acrylates, and the blending amounts of each component were as shown in Table 2. In the resin composition of Example 11, the content (mass %) of the isocyanate group in the crosslinking agent was 0.5 times the content (mass %) of the hydroxyl group in the cellulose polymer. Furthermore, in the same manner as in Example 1, a cured product (cured film) made of the resin composition of Example 11 was formed to a thickness of 15 μm.
[0128] [Example 12] A resin composition of Example 12 was prepared in the same manner as in Example 8, except that the blending amounts of each component were as shown in Table 2. In the resin composition of Example 12, the content (mass %) of the isocyanate group in the crosslinking agent was 1.5 times the content (mass %) of the hydroxyl group in the cellulose polymer. Furthermore, in the same manner as in Example 1, a cured product (cured film) made of the resin composition of Example 12 was formed to a thickness of 15 μm.
[0129] [Example 13] A resin composition of Example 13 was prepared in the same manner as in Example 8, except that the blending amounts of each component were as shown in Table 2. In the resin composition of Example 13, the content (mass %) of the isocyanate group in the crosslinking agent was 3.0 times the content (mass %) of the hydroxyl group in the cellulose polymer. Furthermore, in the same manner as in Example 1, a cured product (cured film) made of the resin composition of Example 13 was formed to a thickness of 15 μm.
[0130] [Comparative Example 1] A resin composition of Comparative Example 1 was prepared in the same manner as in Example 1, except that no crosslinking agent was added and the blending amounts of each component were as shown in Table 3. In the resin composition of Comparative Example 1, no crosslinking agent was used. In the same manner as in Example 1, a cured product (cured film) made of the resin composition of Comparative Example 1 was formed to a thickness of 15 μm.
[0132] [Comparative Example 3] A resin composition of Comparative Example 3 was prepared in the same manner as in Example 5, except that no crosslinking agent was added and the blending amounts of each component were as shown in Table 3. In the resin composition of Comparative Example 3, no crosslinking agent was used. In the same manner as in Example 1, a cured product (cured film) made of the resin composition of Comparative Example 3 was formed to a thickness of 15 μm.
[0134] [Comparative Example 5] As shown in Table 1, 100 parts by mass of the cellulose derivative obtained in the synthesis example and 5 parts by mass of a photoradical initiator (2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropynyl)benzyl)phenyl)-2-methylpropan-1-one (product name: Omnirad 127, manufactured by IGM Resins BV)) were mixed to prepare a resin composition of Comparative Example 5. In the resin composition of Comparative Example 5, no crosslinking agent was used. In the same manner as in Example 1, a cured product (cured film) made of the resin composition of Comparative Example 5 was formed to a thickness of 15 μm.
[0135] [Comparative Example 6] A resin composition of Comparative Example 6 was prepared in the same manner as in Example 12, except that the blending amounts of each component were as shown in Table 3. In the resin composition of Comparative Example 6, the content (mass %) of the isocyanate group in the crosslinking agent was 0.7 times the content (mass %) of the hydroxyl group in the cellulose polymer. In the same manner as in Example 1, a cured product (cured film) made of the resin composition of Comparative Example 6 was formed to a thickness of 15 μm.
[0136] [Comparative Example 7] A resin composition of Comparative Example 7 was prepared in the same manner as in Example 9, except that the blending amounts of each component were as shown in Table 3. In the resin composition of Comparative Example 7, the content (mass %) of the isocyanate group in the crosslinking agent was 0.7 times the content (mass %) of the hydroxyl group in the cellulose polymer. In addition, in the same manner as in Example 1, a cured product (cured film) made of the resin composition of Comparative Example 7 was formed to a thickness of 15 μm.
[0137] [Table 1]
[0138] [Table 2]
[0139] [Table 1]
[0140] [evaluation] (Transmittance of light with a wavelength of 380 nm, total light transmittance and degree of polarization) The polarizing plates obtained in Examples 1 to 13 and Comparative Examples 1 to 7 were cut into pieces measuring 50 mm×50 mm with a Thomson blade. The TAC film side was then attached to glass via a pressure sensitive adhesive. The release film was peeled off from the polarizing plate attached to the glass, and the total light transmittance and polarization degree of the polarizing plate (laminate of protective layer, polarizer, adhesive layer and TAC film) was measured using an ultraviolet-visible spectrophotometer (model: UV-2550, manufactured by Shimadzu Corporation). In addition, the release film was peeled off from the release film with protective layer, and the transmittance of light with a wavelength of 380 nm of the protective layer (cured film) was measured in the same manner as above. The results are shown in Tables 4 to 6.
[0141] (Hayes) The polarizing plates obtained in Examples 1 to 13 and Comparative Examples 1 to 7 were cut into pieces measuring 50 mm×50 mm with a Thomson blade. The TAC film side was then attached to glass via a pressure sensitive adhesive. The release film with protective layer was peeled off from the polarizing plate attached to the glass, and the haze of the polarizing plate (laminate of protective layer, polarizer, adhesive layer and TAC film) was measured using a haze meter (model name: NDH-5000W, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K7136:2000 "Determination of haze of plastics-transparent materials". The results are shown in Tables 4 to 6.
[0142] (Pencil hardness) The polarizing plates obtained in Examples 1 to 13 and Comparative Examples 1 to 7 were cut into pieces measuring 50 mm×50 mm with a Thomson blade. The release film with protective layer was peeled off from the polarizing plate, and the pencil hardness of the polarizing plate (laminate of polarizer, adhesive layer and TAC film) was measured at room temperature (25°C) using a scratch coating hardness tester (model: AD-3110, manufactured by Ueshima Seisakusho Co., Ltd.) in accordance with JIS K5400-1900 "General Test Method for Paints". The load used for measuring the pencil hardness was 500 g. The results are shown in Tables 4 to 6.
[0143] (Scratch resistance) The polarizing plates obtained in Examples 1 to 13 and Comparative Examples 1 to 7 were cut into pieces measuring 50 mm×50 mm with a Thomson blade. The TAC film side was then attached to glass via a pressure sensitive adhesive. The release film with the protective layer was peeled off from the polarizing plate attached to the glass. The exposed surface (the surface of the protective layer (the surface made of a resin composition) of the polarizing plate) was rubbed back and forth 10 times at a speed of 120 mm / sec with steel wool #0000 (product name: Bonstar, manufactured by Japan Steel Wool Co., Ltd.) while applying a load of 300 g. If there were 2 scratches or less, the evaluation was "◎", if there were 3 to 5 scratches, the evaluation was "○", if there were 6 to 10 scratches, the evaluation was "△", and if there were 11 scratches, the evaluation was "×". If there were 5 scratches or less (if it was "◎" or "○"), it was considered to have passed. The results are shown in Tables 4 to 6.
[0144] (Adhesion) The polarizing plates obtained in Examples 1 to 13 and Comparative Examples 1 to 7 were cut into pieces measuring 50 mm×50 mm with a Thomson blade. The TAC film side was then attached to glass via a pressure sensitive adhesive. The release film with the protective layer was peeled off from the polarizing plate attached to the glass. On the exposed surface (the surface of the protective layer (the surface made of the resin composition) of the polarizer), 100 squares each having a size of 1 mm were cut with a cutter knife, and cellophane tape was applied to the squares. Thereafter, the cellophane tape was peeled off from the polarizing plate, and the number of protective layers remaining in the grid patterns that had not been peeled off was counted. The case where 90 or more of 100 pieces of the protective layer in the grid pattern remained unpeeled was rated as passing, and was judged to have excellent adhesion. The results are shown in Tables 4 to 6.
[0145] (Mandrel test) The polarizing plates obtained in Examples 1 to 13 and Comparative Examples 1 to 7 were cut into pieces measuring 50 mm×50 mm with a Thomson blade. The release film with the protective layer was peeled off from the polarizing plate. Using a bending tester (Ueshima Seisakusho Co., Ltd.), a mandrel test was performed at room temperature in which the polarizing plate (laminate of adhesive layer and polarizer) from which the release film with protective layer had been peeled off was folded once with the protective layer side facing outward and returned to a flat shape. The mandrel test was performed in accordance with JIS K 5400-1900 "General test method for paints." After the mandrel test, the protective layer was checked for the presence or absence of cracks. If there were no cracks, it was rated as "○", and if there were cracks, it was rated as "×". The results are shown in Tables 4 to 6.
[0146] (Heat and humidity resistance test) The polarizing plates obtained in Examples 1 to 13 and Comparative Examples 1 to 7 were cut into pieces measuring 50 mm×50 mm with a Thomson blade. The TAC film side was then attached to glass via a pressure sensitive adhesive. The release film with the protective layer was peeled off from the polarizing plate attached to the glass. The polarizing plate from which the protective layer-attached release film had been peeled off was stored in a thermohygrostat (model: LH-113, manufactured by Espec Corp.) at a temperature of 60° C. and a humidity of 95% for 500 hours.
[0147] (Total light transmittance, polarization degree and b * (Change in The polarizing plates of Examples 1 to 13 and Comparative Examples 1 to 7 after the moist heat resistance test were measured using an ultraviolet-visible spectrophotometer (model: UV-2550, manufactured by Shimadzu Corporation) to determine the total light transmittance, the degree of polarization, and L * a * b* Color space b * The values (amount of change) obtained by subtracting the measured values before and after the moist heat resistance test from the measured values after the moist heat resistance test are shown in Tables 4 to 6. The amount of change in the total light transmittance was within ±3%, the amount of change in the degree of polarization was within ±3%, and * If the change in value was within 3.5, it was determined that the film had excellent resistance to moist heat. The results are shown in Tables 4 to 6.
[0148] (exterior) The polarizing plate after the moist heat resistance test was visually observed, and a case where there was no lifting of the pressure-sensitive adhesive, no cracks in the polarizer, and no peeling of the protective layer was evaluated as "○". A case where there was lifting of the pressure-sensitive adhesive, cracks in the polarizer, and peeling of the protective layer was evaluated as "×". The results are shown in Tables 4 to 6.
[0149] (Heat resistance test) The polarizing plates obtained in Examples 1 to 13 and Comparative Examples 1 to 7 were cut into pieces measuring 50 mm×50 mm with a Thomson blade. The TAC film side was then attached to glass via a pressure sensitive adhesive. The release film with the protective layer was peeled off from the polarizing plate attached to the glass. The polarizing plate from which the protective layer-attached release film had been peeled off was stored in a thermostatic chamber (model name: DKN602, manufactured by Yamato Scientific Co., Ltd.) in an environment at a temperature of 85° C. for 500 hours.
[0150] (Total light transmittance, polarization degree and b * (Change in The polarizing plates of Examples 1 to 13 and Comparative Examples 1 to 7 after the heat resistance test were measured for total light transmittance, polarization degree and L * a * b * Color space b * The values (amount of change) obtained by subtracting the measured values before the heat resistance test from the measured values after the heat resistance test are shown in Tables 4 to 6. The amount of change in the total light transmittance was within ±3%, the amount of change in the degree of polarization was within ±3%, and * If the change in value was within 3.5, it was determined that the heat resistance was excellent. The results are shown in Tables 4 to 6.
[0151] (exterior) The polarizing plate after the heat resistance test was visually observed, and the plate was evaluated as "○" when there was no lifting of the pressure-sensitive adhesive, no cracks in the polarizer, and no peeling of the protective layer. The plate was evaluated as "×" when there was lifting of the pressure-sensitive adhesive, cracks in the polarizer, and peeling of the protective layer. The results are shown in Tables 4 to 6.
[0152] [Table 4]
[0153] [Table 5]
[0154] [Table 2]
[0155] From the results of Tables 4 to 6, the cured products of the resin compositions of Examples 1 to 13 have excellent scratch resistance and bending resistance, and can be used sufficiently as a protective layer for a polarizer. Furthermore, a polarizing plate having the cured products as a protective layer has excellent durability, with small changes in total light transmittance, polarization degree, b*, etc., even when exposed to a high temperature and high humidity environment or a high temperature environment.
[0156] Although the preferred embodiment of the present invention has been described in detail above, the present invention is not limited to such an example. It is clear that a person having ordinary knowledge in the technical field to which the present invention pertains can conceive of various modified or amended examples within the scope of the technical ideas described in the claims, and it is understood that these also naturally fall within the technical scope of the present invention. [Explanation of symbols]
[0157] 10. Release film with protective layer 20 Triacetyl cellulose (TAC) film 30 Polarizer 40 Adhesive composition solution 50 Pre-dried polarizing plate 100 Roller
Claims
1. The composition contains cellulose acylate (A), a polyfunctional (meth)acrylate (B), a crosslinking agent (C), and a photoradical initiator (D), the content of the polyfunctional (meth)acrylate (B) is 100 parts by mass or more and 1000 parts by mass or less based on 100 parts by mass of the cellulose acylate (A); The polyfunctional (meth)acrylate (B) does not contain an isocyanate group, the crosslinking agent (C) has two or more isocyanate groups in one molecule, and the content (mass%) of the isocyanate groups is 0.1 to 5 times the content (mass%) of the hydroxyl groups in the cellulose acylate (A); Further, it contains an ultraviolet absorber (E), The resin composition, wherein the content of the ultraviolet absorber (E) is 14.9 parts by mass or more and 25 parts by mass or less based on 100 parts by mass of the cellulose acylate (A).
2. The resin composition according to claim 1 , wherein the cellulose acylate (A) has at least one selected from the group consisting of acetate, propionate, and butyrate.
3. The resin composition according to claim 1 or 2, wherein the content of the photoradical initiator (D) is 0.1 parts by mass or more and 50 parts by mass or less based on 100 parts by mass of the cellulose acylate (A).
4. The resin composition according to any one of claims 1 to 3, wherein the crosslinking agent (C) has two or more isocyanate groups and one or more acrylate groups in one molecule.
5. A cured product of the resin composition according to any one of claims 1 to 4, A cured product having a transmittance of 10% or less for light with a wavelength of 380 nm.
6. The cured product according to claim 5 , having a thickness of 25 μm or less.
7. A polarizer and a protective layer provided on at least one surface of the polarizer, The protective layer comprises the cured product according to claim 5 .
8. An image display element and polarizing plates provided on one surface and the other surface of the image display element, An image display device, wherein the polarizing plate is the polarizing plate according to claim 7 .
Citation Information
Patent Citations
Cellulose-based light-curing resin for continuous liquid-phase rapid-pulling 3D (three dimensional) printing
CN108003294A
Photo-setting composition based on polyfunctional ethylenic unsaturated cellulosic polymer
JP1989203453A
Thermoplastic cellulose polyurethane polymer
JP1990004815A
Polymer composition
JP1994065349A
Optical film, producing method therefor, polarizing plate and image display apparatus
JP2010044417A